2022
DOI: 10.1155/2022/1280350
|View full text |Cite
|
Sign up to set email alerts
|

Toll-Like Receptors/TNF-α Pathway Crosstalk and Impact on Different Sites of Recurrent Myocardial Infarction in Elderly Patients

Abstract: Background. Recurrent myocardial infarction is associated with increased mortality. Risk and predictive factors of recurrent myocardial infarction in elderly patients after coronary stenting are not well known. This research sought to investigate the effects of proinflammatory cytokines and toll-like receptor on recurrent myocardial infarction after coronary stenting in elderly patients. Methods. We measured the levels of toll-like receptor 2 (TLR2), toll-like receptor 3 (TLR3), toll-like receptor 4 (TLR4), tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 56 publications
(62 reference statements)
1
2
0
Order By: Relevance
“…As TNF-α is released upon plaque rupture 21 , measurements of TNF-α could be assumed to be a more accurate way of studying the physiological processes, but this was not seen as a good alternative, as TNF-α has been reported to have a short half-life in stored samples 16 . However, studies measuring both TNF-α and sTNFRs show similar trends for these markers 14 , 15 , 20 , which makes it likely that we would have seen the same results also with TNF-α in our patients.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…As TNF-α is released upon plaque rupture 21 , measurements of TNF-α could be assumed to be a more accurate way of studying the physiological processes, but this was not seen as a good alternative, as TNF-α has been reported to have a short half-life in stored samples 16 . However, studies measuring both TNF-α and sTNFRs show similar trends for these markers 14 , 15 , 20 , which makes it likely that we would have seen the same results also with TNF-α in our patients.…”
Section: Discussionsupporting
confidence: 66%
“…It has also been associated with increased risk for heart failure 11 , incident myocardial infarction 12 and cardiovascular death 13 in population-based studies. Increased levels have also been found in patients with recurrent ventricular arrhythmia 14 or recurrent myocardial infarction 15 after coronary stenting. However, only a few studies so far have measured sTNFRs in patients with acute ST-segment elevation myocardial infarction (STEMI) 16 18 .…”
Section: Introductionmentioning
confidence: 97%
“…Li et al found that the increased expression of TLR2 supported the point that proinflammatory TLR was involved in the pathogenesis of MI. TLR2 was a predictive biomarker in elderly patients with MI ( 38 ). Consequently, IL1B and TLR2 were important biomarkers of MI.…”
Section: Discussionmentioning
confidence: 99%